China's Health Diplomacy Strategy During COVID-19 Crisis 2020-2022 - Kartodirdjo, Azzizah; Rahman, Muhammad Sigit Andhi (Insignia: Journal of International Relations, 2024)
In time of crisis like COVID-19 outbreak, China’s health diplomacy has become a spotlight in terms of its international momentum in dealing the virus. This research is important to know how health diplomacy can be used as an effective foreign policy. The research question in this paper asks how did China conduct health diplomacy during the COVID-19 crisis from 2020 to 2022. This research used descriptive and literature research methods by collecting secondary data from related research and international organization, WHO, as main source for COVID-19 data. The data were analyzed using neoclassical realism theory. Not to mention, there is not much literature that analyzes China's before until the recent "New Normal" situation. When COVID-19 emerge, it simultaneously transforms its health diplomacy into vaccine diplomacy that begins from the first outbreak of the virus. It underwent scrutiny and criticism from other countries as they were sceptical about whether it is purely on conducting global health diplomacy or China's way of promoting a strategic framework. It also has a clear intention that its action is also to appease the world view toward its role since the virus is from Wuhan, a city in China. This research concludes international system can affect state behaviour toward its relations with other countries by examining China's health diplomacy. Keywords: China’s Foreign Policy, Global Health Diplomacy, Vaccine Diplomacy